2017
DOI: 10.2147/ijn.s140325
|View full text |Cite
|
Sign up to set email alerts
|

Drug delivery approaches for breast cancer

Abstract: Breast cancer is one of the most common cancers affecting women worldwide. The controlled release of drugs to the precise site of the disease using a nanocarrier vehicle increases the therapeutic efficiency of the drugs. Nanotechnology-based approaches used to endorse clinical improvement from a disease also help to understand the interaction of malignant cells with their microenvironment. Receptor-based targeting is another approach for drug delivery which is undergoing clinical trials. Nanoparticles (NPs) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(109 citation statements)
references
References 105 publications
1
106
0
2
Order By: Relevance
“…Tremendous efforts have been made in discovering and synthesizing inhibitors for efflux pumps to re-sensitize resistant cancer cells to chemotherapeutic drugs. One of the few strategies that were successful in inhibiting the active efflux of ABC transporters is the encapsulation of drugs with nanoparticles [30, 38, 39]. In the present study, we, interestingly, found that the combined treatment inhibited the growth of the DTX resistant PC3 cells by down-regulating the ABCB1, ABCC1 and ABCG2 genes at both protein and mRNA levels.…”
Section: Discussionsupporting
confidence: 55%
“…Tremendous efforts have been made in discovering and synthesizing inhibitors for efflux pumps to re-sensitize resistant cancer cells to chemotherapeutic drugs. One of the few strategies that were successful in inhibiting the active efflux of ABC transporters is the encapsulation of drugs with nanoparticles [30, 38, 39]. In the present study, we, interestingly, found that the combined treatment inhibited the growth of the DTX resistant PC3 cells by down-regulating the ABCB1, ABCC1 and ABCG2 genes at both protein and mRNA levels.…”
Section: Discussionsupporting
confidence: 55%
“…The controlled release of drugs to a precise site of a disease using a nanocarrier vehicle increases their therapeutic efficiency . Carbon‐based nanomaterials are potential candidates for various applications in medicine generally and anticancer therapy, in particular.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor pathophysiology manifests with characteristic changes such as in pH, enzyme activity, or redox properties . Controlled ‐ release delivery systems based on nanotransporters delivering a bioactive agent to the target site at a controlled concentration could increase the therapeutic efficiency of the drugs .…”
Section: Resultsmentioning
confidence: 99%
“…Many clinical trials have reported that treatment of HER alone has a low response rate against the extracellular domain of HER-2-positive breast cancer [48][49][50][51]. On the other hand, a combination therapy with chemotherapeutic drugs promotes not only the inhibition of tumor growth, but also the overall survival rate of breast cancer patients [52][53][54][55][56]. To determine the synergistic effect of combination therapy with HER and DOX, the viability of DL-CNPs in SK-BR-3 cells was compared with that in MDA-MB-231 cells.…”
Section: Evaluation Of Active Targeting and Intracellular Accumulatiomentioning
confidence: 99%